Greenhouse gas emission mitigation for the sustainable palm oil industry - Bimo Yudo Kristanto; Ahyahudin Sodri; Evi Frimawaty (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: The palm oil industry faces increasing pressure to address its environmental impacts, particularly greenhouse gas (GHG) emissions from operational activities. This study conducts a comprehensive analysis of GHG emissions from palm oil operations using ISO 14064-1 standards at PT. X in Muaro Jambi, Indonesia. The research is particularly relevant given Indonesia's ENDC target of 31.89% unconditional emission reduction by 2030, to which the palm oil sector can contribute through methane capture and energy efficiency measures. Methods: The research employed a case study design with complete enumeration of emission sources, combining primary field measurements and secondary data. Emission calculations followed ISO 14064-1 integrated with IPCC 2006 guidelines, covering Scope 1, 2, and 3. Primary data included fertilizer usage (278.99 tons N/year), POME volume (113,667 m³/year), COD measurements (25,653.59 mg/L inlet), and fuel consumption (476,661 liters/year). MAC analysis was conducted using a 9.1% discount rate, with uncertainty qualitatively assessed. Findings: Total gross emissions reached 23,616 tCO₂e annually, dominated by Scope 1 (89.8%). POME fugitive emissions constitute the largest source (72.6%), followed by fertilizer (10.1%) and mobile combustion (6.9%). The POME system achieved 96.58% COD removal but generated 17,138.75 tCO₂e from methane. LULUCF sequestration (-48,866.69 tCO₂e) resulted in net emissions of -25,250.74 tCO₂e. MACC analysis identified three economically beneficial options with negative MAC: route optimization with biofuel (-125,210 Rp/tCO₂e), methane capture (-82,398 Rp/tCO₂e), and solar PV installation (-61,986 Rp/tCO₂e). These three options collectively achieve 88.9% of total abatement potential. Conclusion: This study provides the first ISO 14064-1 compliant GHG inventory for an Indonesian palm oil mill. However, the single-case design limits generalizability to other mills with different operational characteristics. Future research should include multi-site studies and quantitative uncertainty assessment. Findings support targeted emission reduction strategies and sector-specific policy development for climate mitigation.Novelty/Originality of this Study: This study integrates ISO 14064-1 GHG inventory with MACC analysis to identify cost-effective emission reduction strategies that support sustainable energy transition in the palm oil industry.